Comparison of thermoluminescence response of different sized Ge-doped flat fibers as a dosimeter. (November 2015) - Begum, Mahfuza; Mizanur Rahman, A.K.M.; Abdul-Rashid, H.A.; Yusoff, Z.; Mat-Sharif, K.A.; Zulkifli, M.I.; Muhamad-Yasin, S.Z.; Ung, N.M.; Kadir, A.B.A.; Amin, Y.M.; Bradley, D.A.
Abstract: Prime dosimetric properties, including dose–response, linearity with dose, energy response, fading and threshold doses were investigated for three different dimension Ge-doped flat fibers. The results of measurement were also compared with two of the more commonly used standard TLD media, TLD-100 (LiF:Mg, Ti−7.5% 6 LiF) and TLD−700 ( 7 LiF:Mg, Ti−99.9% 7 LiF) chips. The flat cross-section samples (60×180) µm 2, (100×350) µm 2 and (200×750) µm 2 were fabricated using the Modified Chemical Vapor Deposition (MCVD) process and pulled from the same "preform." In the study, all flat fiber samples provided good linear dose–response for the photon and electron beams generated using a medical linear accelerator (LINAC), for doses in the range 0.5–8 Gy. Among the samples, the smallest dimension flat fiber provided the best response, with a sensitivity of some 61% and 54%, respectively of that of the TLD-100 and TLD-700 chips. The energy responses of the samples were studied for various photon (6 MV, 10 MV) and electron (6 MeV, 9 MeV) beam energies. TL fading of around 20% was observed over a period of thirty (30) days. These favorable TL characteristics point towards promising development of Ge-doped flat fibers for use in radiotherapy dosimetry. Highlights: The thermoluminescences (TL) of different sizes of Ge-doped flat fibers were investigated. Ge-doped flat fibers were fabricated using the Modified Chemical Vapor Deposition (MCVD) process. The TL responses of the flat fibers have been compared with standard TLD-100 and TLD-700 chips. Among the flat fiber samples, the smallest dimension flat fiber (60×180) µm 2 provided the best response.